PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STUKTURAL NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN SIKAP TERHADAP PEMBELAJARAN MATEMATIKA DAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII.2 SMP NEGERI 5 TAMBANG - Kasmedi, Defriadi; Solfitri, Titi; Yuanita, Putri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aimed to improve learning process, improve attitude toward learning mathematics and mathematics learning outcomes students of class VIII.2 SMP Negeri 5 Tambang in the first semester academic years 2015/2016 by implementing structural approach to cooperative learning model Numbered Heads Together (NHT). The research are two cycles, each cycle has four stages, which are planning, implementation, observation, and reflection. At the end of each cycle, daily tests are carried out. Data collected through observation, attitude questioner towards learning mathematics and tests in the form of daily tests. Observation is used to collect teacher and student activities during learning process, test is used to collect mathematic outcomes. Questioner attitude toward learning mathematics given before and after the action to collect the data of attitude toward learning mathematics and analyzed using the Wilcoxon signed-rank test. The results show the activity of teachers and students in learning has been in line with the lesson plan. Most of the students have participated activity and be positive in the learning process. The result show that improvement in students learning outcomes was 35,71% on the basic score became 71,42% in the first cycle and 88,71% in the second cycle. basic Analyze questioner attitude towards learning mathematics for all indicators and for each indicator based on testing criteria Ho is rejected in the other word of attitude towards learning mathematics student, increased after the actions. Results of this research indicate that the application of Structural Approach to Cooperative Learning Model Numbered Heads Together (NHT) can improve learning process, improve attitude toward learning mathematics and improve the mathematics learning outcomes math class VIII.2 SMP Negeri 5 Tambang in the first semester academic years 2015/2016.Keywords: Learning outcome, Attitude toward learning mathematics, Cooperative learning, Numbered Heads Together.2